Effect of COVID-19 Pandemic on NSE Nifty Energy Index - Manivannan Babu; Lourdesraj, A. Antony; Jayapal, Gayathri; Indhumathi, G.; Sathya, J. (International Journal of Energy Economics and Policy, 2022)
The research intends to assess the efficiency of NSE Energy Index-listed firms throughout the COVID-19 before and post pandemic phases, which run from 2019 to 2021. The primary goal of this article was to examine the price movement of corporations in the petroleum, gas, and electricity sectors by employing statistical methods such as descriptive statistics, ADF, and the GARCH (1,1) model, during the period of study. When comparing the post-COVID-19 pandemic era to the pre-COVID-19 pandemic period, certain firms experienced excessive volatility. The energy market’s investor sentiment was significantly higher on the tail events, suggesting that anxious investors raced to put options and paid an exorbitant premium to shield them against unprecedented danger in the energy market.